Pendampingan Pendokumentasian dan Penulisan Sejarah Keluarga di Desa Beji, Ngawen, Gunung Kidul - Mutiah Amini; Uji Nugroho Winardi; Wildan Sena Utama; Bambang Purwanto; Abdul Wahid; Arif Akhyat; Farabi Fakih (Faculty of Cultural Sciences, 2020)
AbstractThe Department of History conducted a community service (PkM) on the topic of documenting and writing family history in Beji Village, Ngawen, Gunung Kidul. The PkM activities are conducted by lecturers and students of History in six months in 2019. Writing and documenting family history is carried out in a participatory method by a coloboration with village residents. The PkM activities were carried out in three stages. First, on May 4, 2019 a dialogue was held between the PkM team and the village stakeholders regarding the plan to write and document the family history of Beji Village. Secondly, on July 15, 2019 the PkM team observed the Nyadran process held by the Beji Village community. Third, the PkM team provides assistance in writing family history and documenting important figures who intersect with culture and art, cultural traditions, and multicultural identities in Beji Village. At the end of this PkM activity, a family history of the village leader has produced, namely the family history of Mbah Yatmo, a prayer reader at the Sadranan ceremony in Beji Village.———-AbstrakDepartemen Sejarah melakukan pengabdian kepada masyarakat (PkM) dengan topik pendokumentasian dan penulisan sejarah keluarga di Desa Beji, Ngawen, Gunung Kidul. Seluruh kegiatan PkM dilakukan oleh dosen dan mahasiswa Ilmu Sejarah dalam waktu enam bulan pada tahun 2019. Penulisan serta pendokumentasian sejarah keluarga yang dilakukan secara partisipatif bersama warga. Kegiatan PkM tersebut dilaksanakan dalam tiga tahapan kegiatan. Pertama, pada 4 Mei 2019 diadakan dialog antara tim PkM dan pemangku desa mengenai rencana penulisan dan pendokumentasian sejarah keluarga Desa Beji. Kedua, pada 15 Juli 2019 tim PkM melakukan observasi proses Nyadran yang diselenggarakan oleh masyarakat Desa Beji. Ketiga, tim PkM melaksanakan pendampingan penulisan sejarah keluarga dan pendokumentasian tokoh penting yang bersinggungan dengan kebudayaan dan kesenian, tradisi kultural, dan identitas multikultural di Desa Beji. Pada akhir kegiatan PkM ini dihasilkan contoh penulisan sejarah keluarga tokoh desa, yaitu sejarah keluarga Mbah Yatmo, seorang pembaca doa dalam upacara Sadranan di Desa Beji.